Empirical bioethics : theoretical and practical perspectives / edited by Jonathan Ives, Michael Dunn and Alan Cribb. - Ives, Jonathan (Senior lecturer in biomedical ethics and law); Dunn, Michael, 1980-; Cribb, Alan (Cambridge bioethics and law., 2017)
Bioethics has long been accepted as an interdisciplinary field. The recent 'empirical turn' in bioethics is however, creating challenges that move beyond those of simple interdisciplinary collaboration, as researchers grapple with the methodological, empirical and meta-ethical challenges of combining the normative and the empirical, as well as navigating the difficulties that can arise from attempts to transcend traditional disciplinary boundaries. Empirical Bioethics: Practical and Theoretical Perspectives brings together contributions from leading experts in the field which speak to these challenges, providing insight into how they can be understood and suggestions for how they might be overcome. Combining discussions of meta-ethical challenges, examples of different methodologies for integrating empirical and normative research, and reflection on the challenges of conducting and publishing such work, this book will both introduce the novice to the field and challenge the expert.